ANALISIS PENGENDALIAN KUALITAS SEBAGAI UPAYA PENGURANGAN PRODUK CACAT DENGAN PENDEKATAN SIX SIGMA, POKA-YOKE DAN KAIZEN - Parwati, Cyrilla Indri; Susetyo, Joko; Alamsyah, Andi (JURNAL GAUNG INFORMATIKA, 2019)
CV. Cita Nasional is a company engaged in processing pure milk into pasteurized fresh milk and homogenization. This research was conducted to analyze defective products using the Six Sigma, Poka -Yoke and Kaizen approaches. Defective products in cup packaging from July 2017 to July 2018 is 20.71% with a target of a maximum of 3% product defects. The purpose of the research is to find out the company?s process capability with DPMO and the level of sigma capability, analyze the factors that cause product disability along with proposed improvements. The method used with Poka-Yoke and determine the action plan in quality control efforts with the Kaizen approach. The result obtained based on the Six Sigma state, namely the Define stage, obtained quality characteristics or CTQ in the form of attribute data 7 characteristic of the causes of disability. The results of the company?s perpormance baseline measurement at the Measure stage of the company were in the condition of 3.383 sigma with DPMO 29.586. The analyze phase is made control map, pareto diagram and makes fish bone diagram to obtain the factors that cause disability. During the improve phase an action plan was developed using the Poka-Yoke approach. In the control phase continuous improvement is done with the Kaizen approach which includes the Five-M checklist concept, 5W+1H (What, Why, Where, When, Who, How) and the Five Step Plan.